(untitled) (City: History, Culture, Society, 2017)
The author "analyzes both the practice of writing "national histories" of cities in southern Ukraine, when the past of a particular locality is viewed from the perspective of a particular ethnic group and the attempt to overcome the limitations caused by this approach. The author notes that in the historiography of the late twentieth - early twentieth centuries. There is a tendency to increase the attention to the history of individual ethnic groups in the "urban space" of the region, to study the contribution of one or another ethnic community to the development of an individual city. It is stated that the thesis about poly-ethnicity and even multi-ethnicity of the "urban space" of Southern Ukraine has become textbook and is applied by almost all researchers of the urban history of the region. However, this does not mean that each of these researchers views the South as a frontier and the southern cities as "outposts" on it. This does not mean, however, that scientists are unanimous in their perception of the cities of the South as "melting pots", which offset the national features of the townspeople, replacing them with other identities. The author emphasizes that while in many cases the creation of "national histories" a particular southern Ukrainian city is considered unique (and often without proper correlation of this uniqueness with the situation in other cities), there is an increasing number of studies in which the development of a particular city (and accordingly its particular ethnic community) is viewed from the perspective of the overall urbanization process. It is noted that the approach to the past of Southern Ukraine as to the history of the Steppe Border, the frontier, which is to a large extent development and transfer to the local soil of FD Turner’s ideas, is becoming more widespread. This approach is guided by the editorial board of the almanack "Frontier Cities", which places the spotlight on the city of the steppe space of Eastern Europe as a complex ethnocultural cross-border. It is conceptually important that the magazine is not limited to the coverage of the "fringe" of one city, thus placing the history of Southern Ukraine in a wider context. The international interdisciplinary project "Black Sea and it’s port cities, 1774-1914, was an exemplary example of the application of such a concept in the South Ukrainian territories. Development, Convergence and Relations with the World Economy"